Wars Within War : Mexican Guerrillas, Domestic Elites, and the United States of America, 1846-1848 - Levinson, Irving W. (Book collections on Project MUSE., 2005)
Traditional characterizations of the 1846-1848 war between the United States and Mexico emphasize the conventional battles waged between two sovereign nations. However, two little-known guerrilla wars taking place at the same time proved critical to the outcome of the conflict. Using information from twenty-four archives, including the normally closed files of Mexico's National Defense Archives, Wars Within War breaks new ground by arguing that these other conflicts proved crucial to the course of events. In the first struggle, a force organized by the Mexican army launched a prolonged campaig.